Grana - Grana (Taylor & Francis, 2026)
Grana is an international journal of palynology and aerobiology. Grana, originally published as Grana Palynologica, was founded in 1954 by Professor Gunnar Erdtman. It is published under the auspices of the Scandinavian Palynological Collegium (CPS) in affiliation with the International Association for Aerobiology (IAA).
FI 0.24
Q4
Keywords: Biological; Earth & Environmental Food Science; Palinología; Aerobiología; Acuerdos transformativos; Transformative agreements; Ontogonía; Medicina (alergología)